Another acidophilic corticolous species of Trichia (Myxomycetes) from Réunion Island - Bortnikov, F.m.; Stephenson, S.l.; Prikhodko, I.s.; Novozhilov, Yu. K. (Phytotaxa, 2025)
A new species of bright-spored myxomycete, Trichia insularis, is described in detail and illustrated with light and scanning electron microscope photographs. This species appeared in a moist chamber culture on the acidic bark of Cryptomeria japonica collected in 2006 on La Réunion Island in the Indian Ocean. The species is part of a complex of closely related species of Trichia that includes T. acetocorticola, T. nubila, and T. pinicola. All of these share the distinctive secondary ornamentation of the capillitial threads that consists of longitudinal thin ridges. However, Trichia insularis differs from all previously described species of Trichia by a unique combination of morphological characters and it also has unique substitutions in its nrSSU, EF1α and mtSSU sequences.